Access to Imported Intermediates and Intra-Firm Wage Inequality - Ying Ge; Tony Fang; Yeheng Jiang (Institute of Labor Economics (IZA), 2019)
We use Chinese firm-level data from the World Bank Investment Climate Survey to examine the link between importing intermediates and intra-firm wage inequality. Our results show that intermediate input importers not only have a significant wage premium but also have a greater intra-firm wage dispersion than non-importing firms. This pattern is robust when we control for productivity and use trade costs as the instruments. We further investigate the mechanism of how importing intermediates might contribute to both inter-firm and intra-firm wage inequality. Our evidence is consistent with three important channels. First, imported intermediate inputs complement skilled labour. Second, intermediates importers are more likely to use performance pay. Third, imported inputs complement innovation and employee training.
Keywords: F16; F63; F66; 330; global production sharing; wage inequality; world bank investment climate survey